Antioxidant Effect of Propolis Against Exposure to Chromium in Cyprinus carpio - Yonar, M. Enis; Yonar, Serpil Mise; Coban, M. Zulfu; Eroglu, Mucahit (Wiley, 2014)
The aim of the present study was to investigate the ameliorative properties of propolis against the toxic effects of chromium (VI) by examining oxidative damage markers such as lipid peroxidation and the antioxidant defence system components in carp (Cyprinus carpio). The fish were exposed to sublethal concentrations of chromium. Propolis was simultaneously administered to chromium-exposed fish. Treatment was continued for 28 days, and at the end of this period, blood and tissue (liver, kidney, spleen, and gill) samples were collected. Levels of malondialdehyde (MDA) and reduced glutathione (GSH) as well as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities were determined in blood and tissues for measurement of oxidant-antioxidant status. The levels of MDA, as an index of lipid peroxidation, increased in blood and tissues. Antioxidant enzyme activities in blood and tissues were modified in chromium groups compared to controls. Simultaneous administration of propolis ameliorated these parameters. The present results suggest that administration of propolis might alleviate chromium-induced oxidative stress. (c) 2011 Wiley Periodicals, Inc. Environ Toxicol 29: 155-164, 2014.
Keywords: fish; Cyprinus carpio; chromium; propolis; oxidative stress; antioxidant status